Safety, Feasibility, and Effects of Short-Term Calorie Reduction during Induction Chemotherapy in Patients with Diffuse Large B-Cell Lymphoma: A Pilot Study - Chia-Chun Tang (Nutrients, 2021)
Short-term calorie reduction (SCR) requires individuals to reduce their calorie intake to less than 50% of normal requirements and has shown good tolerance and potential benefits in prior studies addressing gynecological cancer patients. More studies are needed to further confirm its safety, feasibility, and effects in patients with different cancers, including hematological malignancies. This pilot cohort study with a matched-pair comparison group was registered at ClinicalTrails.gov [201810112RIND]. Adult patients diagnosed with advanced-stage diffuse large-B cell lymphoma were recruited (SCR group) and matched with one comparison patient (comparison group), each in a manner blinded to their outcomes. The SCR group undertook at least two cycles of 48 h water fast along with their chemotherapy R-CHOP. Descriptive analysis and generalized estimating equations were used to analyze the data. Six participants completed multiple cycles of SCR and were compared to their six counterparts in the comparison group. The results showed that SCR is safe and feasible in terms of a high compliance rate and stable nutritional status. The SCR was associated with benefits in post-chemotherapy hematological parameters (i.e., erythrocyte [p < 0.001] and lymphocyte counts [p < 0.001]). More randomized controlled trials are needed to validate the effects of SCR on different types of cancer populations.